Comparison efficacy of oral Nigella sativa seeds and tamsulosin on pain relief and passage of 4 to 10 mm stones of kidney and ureter; a randomized clinical trial - Nahid Shakeri; Sadrollah Mehrabi; Akvan Paymard (Society of Diabetic Nephropathy Prevention, 2022)
Introduction: Urinary stones are the third most common urinary tract disease after urinary tract infections and prostate diseases. Objectives: The aim of this study was to compare efficacy of Nigella sativa seeds and tamsulosin on expulsion and pain relief of ureteral and renal stones smaller than 10 mm. Patients and Methods: In this randomized clinical trial study conducted from March 2018-2019, 80 patients over 18 years old with kidney and ureteral stones sized between 4 to 10 mm were assigned to two groups by the simple random sampling method. In group one, after performing ultrasonography and confirming the presence of 4 to 10 mm stones, one 0.4 mg capsule of tamsulosin was prescribed each night for two weeks. In group 2, one gram of Nigella sativa prescribed every 12 hours after each meal with a glass of water for two weeks. After 2 weeks, patients were visited while a urinary tract sonography was conducted and the modification in size of stones and the existence of residual stones were measured and noted. The pain severity was measured through the visual analog scale (VSA). Data was gathered and analyzed throughout treatment and at the end of the study by the SPSS version 21 software, chi-square and independent t tests. Results: Mean sizes of stones before treatment with Nigella versus tamsulosin groups were 10.3±1.81 and 9.41 ± 1.68 mm respectively (P=0.06). Mean size of stones after treatment with Nigella versus tamsulosin groups were 4.97±4.33 and 5.21 ± 3.63 mm respectively (P=0.39). There was no significant difference between two groups regarding average of the pain score after treatment (P=0.05), but after intervention this score significantly declined in both groups, indicating more substantial in Nigella sativa group (P=0.001). Efficacy of treatment in Nigella and tamsulosin groups was 78.5 and 61.6, respectively (P=0.005). Conclusion: The present study indicated that both Nigella sativa seed and tamsulosin reduce urinary stone size and numbers without significant difference, however stone passage and pain control was more in the group of Nigella sativa. Trial Registration: The trial protocol was approved by the Iranian Registry of Clinical Trial (identifier: IRCT20081011001323N23; https://irct.ir/user/trial/35993/, ethical code; IR.YUMS.REC.1397.155).